Outlining the Roles of Membrane-Foulant and Foulant-Foulant Interactions in Organic Fouling During Microfiltration and Ultrafiltration: A Mini-Review - Xu, Hao; Xiao, Kang; Wang, Xiaomao; Liang, Shuai; Wei, Chunhai; Wen, Xianghua; Huang, Xia (Frontiers in Chemistry, 2020)
Membrane fouling remains a notorious problem in microfiltration (MF) and ultrafiltration (UF), and a systematic understanding of the fouling mechanisms is fundamental for solving this problem. Given a wide assortment of fouling studies in the literature, it is essential that the numerous pieces of information on this topic could be clearly compiled. In this review, we outline the roles of membrane-foulant and foulant-foulant intermolecular interactions in MF/UF organic fouling. The membrane-foulant interactions govern the initial pore blocking and adsorption stage, whereas the foulant-foulant interactions prevail in the subsequent build-up of a surface foulant layer (e.g., a gel layer). We classify the interactions into non-covalent interactions (e.g., hydrophobic and electrostatic interactions), covalent interactions (e.g., metal-organic complexation), and spatial effects (related to pore structure, surface morphology, and foulants size for instance). They have either short- or long-range influences on the transportation and immobilization of the foulant toward the membrane. Specifically, we profile the individual impacts and interplay between the different interactions along the fouling stages. Finally, anti-fouling strategies are discussed for a targeted control of the membrane-foulant and foulant-foulant interactions.